Answer:
The decrease is exponential.
Explanation:
An exponential decrease is something like:
f(x) = A*(r)^x with 0 < r < 1
A linear decrease is something like:
g(x) = -a*x + b with a > 0
First ai general formula.
If you have a quantity Q, decreased by an X%, the new quantity will be:
New Quantity = Q - Q*(X%/100%)
Now let's look at the question:
Suppose that the original price of the computer component is K
And the price as a function of the year is P(y)
Then we know that, in the year zero, the price is K.
P(0) = K
One year after, the price decreases by 2.25%
Then:
P(1) = K - K*(2.25%/100%) = K*(1 - 0.0225)
After another year, we will have another decrease of 2.25%
Then:
P(2) = K*(1 - 0.0225) - K*(1 - 0.0225)*(2.25%/100%)
P(2) = K*(1 - 0.0225)*(1 - 0.0225) = K*(1 - 0.0225)^2
We already can see the pattern, we can expect that in the year y, the price of the component will be:
P(y) = K*(1 - 0.0225)^y
This clearly is an exponential decrease.